Employee Performance in Islamic Economics: AIS, Work Discipline, Organizational Culture and Incentives - Anggrayani, Viki; Agus Kurniawan; Gustika Nurmalia (Penerbit Goodwood, 2025)
Purpose: This study aimed to analyze the effect of accounting information systems, work discipline, organizational culture, and incentives on employee performance from the perspective of Islamic Economics (a study on PT Tunas Dwipa Matra Raden Intan). Methodology/approach: This study used a quantitative approach. Sample selection in this study was performed using a purposive sampling technique, which obtained 30 samples. Results: The results of this study prove that accounting information systems, work discipline, organizational culture, and incentives partially or simultaneously have a positive and significant effect on employee performance in PT Tunas Dwipa Matra. Obtained the value of The coefficient of determination (R Square) was 0.840, which shows that 84% of the variation in the dependent variable can be explained by the independent variables together. Conclusions: Accounting systems, discipline, culture, and incentives improve performance but face issues of teamwork and fairness. Aligning with Islamic values, the company should enhance its systems and apply just, transparent rewards. Limitations: The scope of this study was limited to the influence of accounting information systems, work discipline, organizational culture, and incentives; therefore, other factors that could potentially affect employee performance beyond these variables were not included in the analysis. Contribution: This research contributes to a comprehensive understanding of the influence of accounting information systems, work discipline, organizational culture, and incentives on employee performance at PT. Tunas Dwipa Matra, with an Islamic economic perspective that provides a dimension of ethics and Shariah values in its analysis.